Rio Negro em poemas : reflexos do homem - Lima, Rebeca Soares de (2017)
To look at the Amazon Literature is to realize that the river has a right place, both in the life of city dwellers and in those of the interior. In general, the river is part of the life of those who live in the Amazon region, but it has been noted that one river, in particular, has presented in the literature another, darker and lethal meaning: the Rio Negro. Faced with such a discovery, this research aims to analyze poems that praise the Rio Negro throughout the history of Amazon Literature; Is also intended to compare the interpretations about the Rio Negro, for example, this one is described as dark and dangerous in most lyrical manifestations. As a guide in the analysis, one has the Psychoanalysis, portraying a possible projection of the man towards the river, emphasizing the reflective character of the Black River. In this way, nine poems of eight books were collected between 1899 and 2001, from the following authors: Paulino de Brito, Raimundo Monteiro, Astrid Cabral, Luiz Bacellar, Simão Pessoa, Quintino Cunha, Aldísio Filgueiras and Elson Farias. In the meeting of the poems it was possible to group them into four categories: the Telluric Black River, the lethal one, that of the encounters and that of the Man. Keywords: poetry, Rio Negro, Amazonas